Effects of Trichoderma harzianum and Bacillus subtilis on the root and soil microbiomes of the soybean plant INTACTA RR2 PRO™ - Rigobelo, Everlon Cid; de Andrade, Luana Alves; Santos, Carlos Henrique Barbosa; Frezarin, Edvan Teciano; Sales, Luziane Ramos; de Carvalho, Lucas Amoroso Lopes; Guariz Pinheiro, Daniel; Nicodemo, Daniel; Babalola, Olubukola Oluranti; Verdi, Maria Caroline Quecine; Mondin, Mateus; Desoignies, Nicolas (Frontiers in Plant Science, 2024)
Soybean is a significant export product for several countries, including the United States and Brazil. There are numerous varieties of soybean. Among them, a genetically modified type known as INTACTA RR2 PRO™ has been designed to demonstrate resistance to glyphosate and to produce toxins that are lethal to several species of caterpillars. Limited information is available on the use of Trichoderma harzianum and Bacillus subtilis to promote plant growth and their impact on the plant microbiome. This study aimed to evaluate the effects of these microorganisms on this soybean cultivar by analyzing parameters, such as root and shoot dry matter, nutritional status, and root and soil microbial diversity. The results indicated that treatments with B. subtilis alone or in combination with T. harzianum as seed or seed and soil applications significantly enhanced plant height and biomass compared to the other treatments and the control. No significant differences in phosphorus and nitrogen concentrations were detected across treatments, although some treatments showed close correlations with these nutrients. Microbial inoculations slightly influenced the soil and root microbiomes, with significant beta diversity differences between soil and root environments, but had a limited overall impact on community composition. The combined application of B. subtilis and T. harzianum particularly enhanced plant growth and promoted plant-associated microbial groups, such as Rhizobiaceae, optimizing plant-microbe interactions. Furthermore, the treatments resulted in a slight reduction in fungal richness and diversity.